Physical modelling of lime stabilisation in soft soils around deep excavations. Issue 2 (6th April 2017) - Panchal, J. P.; McNamara, A. M.; Stallebrass, S. E.
Abstract : The availability of space above ground decreases as cities expand, causing a demand for very deep underground structures so developments must mitigate the risk of damaging adjacent buildings. This is especially critical in soft clays where ground movements are considerable and can extend far beyond the excavation site. This paper investigates the efficacy of a shallow lime stabilised clay layer on reducing heave and the settlement profile behind an embedded retaining wall. Centrifuge modelling at 160  g was used to observe surface and subsurface soil movements of a 12 m deep excavation ( H ) supported by a retaining wall of 8.8 m embedment at prototype scale. Since this research focussed on measures used to minimise heave the model comprised a high stiffness, fully supported 'rigid wall' to eliminate ground movements attributed to wall deformation. A direct comparison between a reference test, with no improvements and a test comprising H /2 thick 5% lime stabilised layer indicated that the lime treatment increased the excavation stability by a factor of three.